“Darurat Pelecehan Seksual” Menyanyi sebagai Metode Meningkatkan Pemahaman Seks Edukasi pada Anak - Lukman Hakim; Selly Candra Ayu (Jurnal Psikologi Tabularasa, 2023)
ABSTRACTSexual abuse of children is a case of violence that must be anticipated because it occurs more frequently and most of the perpetrators are people close to them. Seksual violence will have an impact on children’s psychology, both in the short and long term. It is important to provide an understanding of sex education in children to anticipate seksual abuse. This study aims to apply sex education methods that are easy to apply and fun for children. The method in thisstudy used a quasi-experiment with a one group pretest-posttest design, data collection using a picture checklist, the treatment carried out in the study was singing. The subjects in this study were 5th and 6th grade students of SDN 1 Siwalankerto. The results of thisstudy showed that the subjects were able to understand whatseksual harassment is, how to protect themselves, which body parts can be touched and should not be touched by others. Understanding how to protect themselves from seksual harassment, and understanding the importance of dealing with the potential for seksual harassment, by singing the subject understands the content of the message conveyed, and is enthusiastic about learning to protect themselves and love themselves. The results of the difference test (Z) = -5.175 with a significant value of 0.001 (p d” 0.05) is smaller than 0.05, which means there is an increase in knowledge about sex education. From the research results, the singing method can be a solution to provide an understanding of sex education for children.ABSTRACTPelecehan seksual pada anak merupakan kasus tindak kekerasan yang harus di antisipasi karena semakin sering terjadi dan kebanyakan pelakunya merupakan orang terdekat. Pelecehan seksual akan berdampak pada psikis anak, baik dalam jangka pendek maupun jangka panjang. Pentingnya memberikan pemahaman terkait seks edukasi pada anak untuk mengantisipasi terjadinya pelecehan seksual. Pada penelitian ini bertujuan untuk menerapkan metode seks edukasi yang mudah diterapkan dan menyenangkan untuk anak. Metode dalam penelitian ini menggunakan quasi eksperimen dengan desain one group pretest-posttest design, pengambilan data menggunakan ceklist gambar, treatmen yang dilakukan dalam penelitian adalah dengan bernyanyi. Subjek dalam penelitian ini adalah siswa kelas 5 dan 6 SDN 1 Siwalankerto. Hasil dari penelitian ini subjek mampu memahami apa itu pelecehan seksual, bagaimana cara menjaga diri, bagian tubuh mana yang boleh disentuh dan tidak boleh disentuh orang lain. Memahami cara melindungi diri dari pelecehan seksual, serta memahami pentingnya menghadapi potensi terjadinya pelecehan seksual, dengan bernyanyi subjek lebih memahmai isi dari pesan yang disampaikan, dan antusias belajar menjaga diri serta menyayangi diri sendiri. Hasil uji beda (Z)= -5.175 dengan nilai signifikan 0.000 (p 0.05) lebih kecil dari 0.05 yang berarti ada peningkatan pengetahuan tentang seks edukasi. Dari hasil penelitian metode menyanyi dapat menjadi solusi unutk memberikan pemahaman terkiat seks edukasi pada anak.